Association of orthostatic blood pressure response with incident heart failure: The Framingham Heart Study - Shrout, Tara A.; Pan, Stephanie; Mitchell, Gary F.; Vasan, Ramachandran S.; Xanthakis, Vanessa (PloS one, 2022)
Orthostatic hypotension (OH) and hypertension (OHT) are aberrant blood pressure (BP) regulation conditions associated with higher cardiovascular disease risk. The relations of OH and OHT with heart failure (HF) risk in the community are unclear and there remains a paucity of data on the relations with HF subtypes [HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF)]. Relate OH and OHT with HF risk and its subtypes. Prospective observational cohort. Community-based individuals in the Framingham Heart Study Original Cohort. 1,914 participants (mean age 72 years; 1159 women) attending examination cycle 17 (1981-1984) followed until December 31, 2017 for incident HF or death. OH or OHT, defined as a decrease or increase, respectively, of ≥20/10 mmHg in systolic/diastolic BP upon standing from supine position. At baseline, 1,241 participants had a normal BP response (749 women), 274 had OH (181 women), and 399 had OHT (229 women). Using Cox proportional hazards regression models, we related OH and OHT to risk of HF, HFrEF, and HFpEF compared to the absence of OH and OHT (reference), adjusting for age, sex, body mass index, systolic and diastolic BP, hypertension treatment, smoking, diabetes, and total cholesterol/high-density lipoprotein. On follow-up (median 13 years) we observed 492 HF events (292 in women; 134 HFrEF, 116 HFpEF, 242 HF indeterminate EF). Compared to the referent, participants with OH [n = 84/274 (31%) HF events] had a higher HF risk (Hazards Ratio [HR] 1.47, 95% CI 1.13-1.91). Moreover, OH was associated with a higher HFrEF risk (HR 2.21, 95% CI 1.34-3.67). OHT was not associated with HF risk. Orthostatic BP response may serve as an early marker of HF risk. Findings suggest shared pathophysiology of BP regulation and HF, including HFrEF.